Listening Overlooked: An Audit of Listening as a Category in the Public Sphere - Lacey, Kate (Javnost-The Public, 2011)
This article suggests how listening might be rethought as foundational to theories of the public sphere and the forms of communication that take place in public. Listening, as a communicative and participatory act, is necessarily political but political theory tends to concentrate on the rights and responsibilities of speech and expression. Attending to the rights and responsibilities of those listening opens up surprisingly far-reaching speculations about the guarantee of plurality and offers a powerful conceptual corrective to communication models based on an idealised dialogic encounter. The analytical separation of “listening out” – an attentive and anticipatory communicative disposition – from “listening in” – a receptive and mediatised communicative action – opens up a space to consider mediated listening as an activity with political resonance. Rethinking audiences as listening publics, offers productive new ways to address the politics, ethics and experience of political communication and public life.